2018
DOI: 10.12957/demetra.2018.34989
|View full text |Cite
|
Sign up to set email alerts
|

Práticas Alimentares De Agricultores Familiares No Município De Petrópolis-Rj

Abstract: Objetivo: Identificar práticas de consumo e comportamento alimentar saudáveis e não saudáveis de agricultores familiares do bairro Caxambu, no município de Petrópolis-RJ. Metodologia: Trata-se de estudo transversal realizado com amostra de 35 agricultores familiares. Informações foram obtidas por meio de entrevistas, utilizando um questionário estruturado e padronizado. As práticas alimentares foram avaliadas a partir dos itens do questionário utilizado pelo SISVAN associados às frequências de consumo do quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It is important to mention that other studies that evaluated food consumption in rural areas identified that many individuals in these regions maintained their consumption of traditional foods, such as rice, breads, leafy beans, beans, cow’s milk, animal fats, margarine, sugar, cassava flour and coffee [ 30 , 57 , 91 93 ]. However, it is also possible to notice an increase in consumption of industrialized foods [ 30 , 31 , 93 96 ], which demonstrates that factors associated with globalization also affect eating habits in rural areas [ 30 , 66 , 94 – 97 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to mention that other studies that evaluated food consumption in rural areas identified that many individuals in these regions maintained their consumption of traditional foods, such as rice, breads, leafy beans, beans, cow’s milk, animal fats, margarine, sugar, cassava flour and coffee [ 30 , 57 , 91 93 ]. However, it is also possible to notice an increase in consumption of industrialized foods [ 30 , 31 , 93 96 ], which demonstrates that factors associated with globalization also affect eating habits in rural areas [ 30 , 66 , 94 – 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that other studies that evaluated food consumption in rural areas identified that many individuals in these regions maintained their consumption of traditional foods, such as rice, breads, leafy beans, beans, cow’s milk, animal fats, margarine, sugar, cassava flour and coffee [ 30 , 57 , 91 93 ]. However, it is also possible to notice an increase in consumption of industrialized foods [ 30 , 31 , 93 96 ], which demonstrates that factors associated with globalization also affect eating habits in rural areas [ 30 , 66 , 94 – 97 ]. Although agricultural residents have options to obtain their food from their plantations or through community sharing, they may have limited availability of healthy food due to the long distances from places that sell food, in addition to the high prices of some items in small local markets, low availability of transport for access to cheaper products and difficulty of storing these foods [ 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%